A Status Update on Pharmaceutical Analytical Methods of Aminoglycoside Antibiotic: Amikacin. (2nd March 2022) - Raut, Adishri; Sharma, Dhvani; Suvarna, Vasanti
Abstract: Amikacin (AMK) is one of the commonly used aminoglycoside antibiotics, introduced for clinical use in patients suffering from bacterial infections especially life-threatening gram-negative infections. Due to lack of chromophore in the molecule, the detection of AMK during analysis is a challenge. Thus, pre and post-column derivatization techniques are generally used for AMK estimation. This review focuses on different analytical methods used for detection and quantification of AMK in pure or fixed dose combination pharmaceutical formulations and biological samples. Various reported methods described in the literature include high-performance liquid chromatography techniques, pulsed electrochemical detection techniques, Chemiluminescence techniques, Capillary electrophoresis and immunological methods. High-performance-liquid-chromatography based methods with UV/Vis spectrophotometric, fluorescence and mass spectrometric detection are the most prevailing methods employed for the analysis of AMK. This review could be of significant importance in the area of future AMK analytical method development studies.